Ples mrtvaca na beramskim freskama u crkvi sv. Marije na Škrilinah - Lenković, Mirela (Array, 2018)
The Danse Macabre as an iconographic theme appears in the Middle Ages across all of Europe carrying within it a message of the equality among people regardless of their station in life. Medieval artists used the various templates available to them: Biblia pauperum, Meditationes Vitae Christi, Legenda aurea, artistic templates, woodcuts, illuminated manuscripts, and the like. Scenes of the dying and death of ordinary people were not a theme of iconographic content prior to the Late Middle Ages, but rather begin to appear in the 14th century. There emerge at that time several categories of iconographic deaths. The Danse Macabre of the Beram frescoes (in the Chapel of sv. Marija na Škrilinah, 1474) contributes immeasurably to the artistic heritage of the Middle Ages as well as to Croatian cultural heritage.